An approach for integrating water use assessment into the design processes of the Indonesian batik industry - Ida Nursanti; Alison McKay; Richard Chittenden (International Journal of Sustainable Engineering)
Strategic product design and the optimisation of the structural features of a design can be an effective way to minimise resource consumption. Because water is one of the resources used in the production process, the principles of sustainable product design can be applied to water use. However, limited research has been conducted to date. This study introduces an approach for integrating water use assessment into the design processes of the Indonesian batik industry. This approach allows batik designers to explore alternative production scenarios for a given concept design and quantify the water use for each scenario. In turn, this enables them to make better-informed decisions regarding the best concept design and production process in terms of water use. The efficacy of this approach was demonstrated by its application to an example batik fabric. This approach assists in defining production scenarios based on key characteristics of the design, such as the colours in the design, and enables the quantification of water use in batik production through process simulations. This contribution has the potential to enhance design processes by allowing batik designers to analyse water use when creating batik designs and providing opportunities to develop strategies for reducing water use.